The Effect of Store Atmosphere and Customer Experience on Customer Loyalty with Customer Engagement as An Intervening Variable on Customers of Noms Coffee Branch, Jl. Soekarno Hatta, Semarang City (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of store atmosphere and customer experience on customer loyalty, with customer engagement as an intervening variable on customers of Noms Kopi Branch on Jl. Soekarno Hatta, Semarang City. This study is quantitative in nature. The population studied includes customers of Noms Kopi Branch Jl. Soekarno Hatta. The sampling technique used is Purposive Sampling, with a sample size of 80 respondents. This study applies Partial Least Square Analysis using software Smart PLS Version 3. The results show that Store Atmosphere does not have a significant influence on customer engagement and customer loyalty. Customer experience has a positive and significant effect on customer engagement and customer loyalty. On the other hand, customer engagement shows a positive and significant effect on customer loyalty. Customer engagement cannot mediate the relationship between store atmosphere and customer loyalty, whereas in the relationship between customer experience and customer loyalty, customer engagement can mediate.
Keywords: store atmosphere; customer experience; customer engagement; customer loyalty